A coarse-grained concurrent multiscale method for simulating brittle fracture. (1st November 2022) - Niknafs, Soheil; Silani, Mohammad; Concli, Franco; Aghababaei, Ramin
Graphical abstract: Abstract: This paper proposed a concurrent multiscale method for modeling crack propagation in brittle solids. The method couples the continuum finite element domain with a recently-developed coarse-grained atomistic potential, which has been developed to simulate crack nucleation and propagation within the molecular dynamics domain. The main advantage of this potential is to suppress dislocation nucleation from the crack tip which significantly eases the coupling procedure. In this multiscale framework, complexities like large deformation, crack nucleation and propagation are simulated in the atomistic domain while the rest such as elastic wave propagation and boundary conditions are modeled in the continuum domain. As a result, the atomistic area will be limited around the cracking zone which increases the computational efficiency. Two examples of edge crack propagation and sliding surfaces in contact are presented and compared with the fully atomistic models to verify and check the efficiency of the proposed multiscale method. The comparison shows that the proposed method can accurately capture the crack formation while the computation cost reduces significantly.